Differences In the Effect Between Balance Training And Strengthening Exercises On Pain And Functional Ability In Patients With Genu Osteoarthritis - Fazrina, Gina; Gunawan, Dindin Hardi; Mahasih, Teki; Adijanto, Adijanto; Jaenudin, Jaenudin; Sari, Elisa Wantika (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Objective: to determine whether there is a difference in the effect between balance training and strengthening exercises on pain and functional ability in knee osteoarthritis. Design: two group pre-test and post-test. Subjects & Treatments: 16 patients (n=16) with knee osteoarthritis who met the study criteria were divided into 2 groups. Group I was given balance training while group II was given strengthening training. Each was treated 12 times, 2 times a week. Place of Study: Physiotherapy Room, Medical Rehabilitation Installation of RSUD 45 Kuningan. Time: November 7, 2022 to February 15, 2023. Measurement Tools: WOMAC Index. Analysis: Non parametric test, Wilcoxon & Mann Whitney Test. Results: Wilcoxon pre-post pain test of group I showed p = 0.020 (p<0.05) and Wilcoxon pre -post functional ability test showed p = 0.101 (p>0.05) which means there is an effect of providing balance training on pain but no effect on functional ability. The Wilcoxon pre-post pain test for group II showed p = 0.016 (p <0.05) and the Wilcoxon pre -post functional ability test showed p = 0.119 (p>0.05) which means there is an effect of strengthening exercises on pain but no effect on functional ability. Mann Whitney test of pain between the two groups showed p = 0.832 (p>0.05) and functional ability showed p = 0.713 (p>0.05) which means there is no difference in effect between treatment groups I and II. Conclusion There is no difference in the effect between balance training and strengthening exercises on pain and functional ability in knee osteoarthritis.